2014
DOI: 10.1021/es501547b
|View full text |Cite
|
Sign up to set email alerts
|

Deepwater Horizon Oil in Gulf of Mexico Waters after 2 Years: Transformation into the Dissolved Organic Matter Pool

Abstract: Recent work has shown the presence of anomalous dissolved organic matter (DOM), with high optical yields, in deep waters 15 months after the Deepwater Horizon (DWH) oil spill in the Gulf of Mexico (GOM). Here, we continue to use the fluorescence excitation-emission matrix (EEM) technique coupled with parallel factor analysis (PARAFAC) modeling, measurements of bulk organic carbon, dissolved inorganic carbon (DIC), oil indices, and other optical properties to examine the chemical evolution and transformation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 45 publications
(101 reference statements)
7
40
0
Order By: Relevance
“…These compounds were negatively correlated with peak M*, fluorescence ratios A/T, C/T and M/T and BIX and positively with peak T*, a 254* and HIX. These findings are in agreement with the fact that some polyphenols fluoresce in an area relatively close to the protein-like substances region 58, 71 . Furthermore, it was suggested that hydrocarbons are detected in the peak T* region 27 .…”
Section: Resultssupporting
confidence: 91%
“…These compounds were negatively correlated with peak M*, fluorescence ratios A/T, C/T and M/T and BIX and positively with peak T*, a 254* and HIX. These findings are in agreement with the fact that some polyphenols fluoresce in an area relatively close to the protein-like substances region 58, 71 . Furthermore, it was suggested that hydrocarbons are detected in the peak T* region 27 .…”
Section: Resultssupporting
confidence: 91%
“…Investigations into crude oil in the Gulf of Mexico have also associated fluorescence signatures similar to those in Fig. 3 with the presence of hydrocarbons (Bianchi et al, 2014). These observations suggest that waters impacted by hydrocarbons (e.g., flowback, produced water, and crude oil in ocean) may have a similar fluorescence signature characterized by blue-shifted intensity (predominantly less than 400 nm).…”
Section: Dissolved Organic Matter Fractionationmentioning
confidence: 63%
“…The general absorbance features in this range of wavelengths of the sand patty-derived DOM were reminiscent of other reports of DOM emanating from the weathering of the Deepwater Horizon oil. 53 Most notably, the quantitative increase in aromatic DOM constituents formed as a result of natural weathering processes seems to be a generalizing feature of oil decomposition. 24 An assessment of the aerobic biodegradability of sand patty-derived DOM was examined by comparing the rate of oxygen consumption in sediment samples amended with dark or irradiated DOM, whole sand patty material or only endogenous organic matter.…”
Section: Discussionmentioning
confidence: 99%